Part B. Calculate the enthalpy of the reaction
4B(s) + 3O2(g) → 2B2O3(s)
Given the following pertinent information:
1. B2O3(s) + 3H2O(g) → 3O2(g) + B2H6(g), ΔH°A = + 2035 kJ
2. 2B(s) + 3H2(g) → B2H6(g), ΔH°B = + 36 kJ
3. H2(g) + 1/2 O2(g) → H2O(l), ΔH°C = − 285 kJ
4. H2O(l) → H2O(g), ΔH°D = + 44 kJ
Express your answer with the appropriate units.
Hess's law states that "the heat released or absorbed in a chemical process is the same whether the process takes place in one or in several steps." It is important to recall the following rules:
1. When two reactions are added, their enthalpy values are added.
2. When a reaction is reversed, the sign of its enthalpy value changes.
3. When the coefficients of a reaction are multiplied by a factor, the enthalpy value is multiplied by that same factor.
Frequently Asked Questions
What scientific concept do you need to know in order to solve this problem?
Our tutors have indicated that to solve this problem you will need to apply the Hess's Law concept. You can view video lessons to learn Hess's Law. Or if you need more Hess's Law practice, you can also practice Hess's Law practice problems.